2016
DOI: 10.1186/s12909-016-0543-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between resident physicians’ publications and clinical performance during residency training

Abstract: BackgroundBoth research and clinical medicine requires similar attributes of efficiency, diligence and effective teamwork. Furthermore, residents must succeed at scholarship and patient care to be competitive for fellowship training. It is unknown whether research productivity among residents is related to broad measures of clinical achievement. Our goal was to examine associations between the quantity of internal medicine residents’ publications and validated measures of their knowledge, skills and multi-sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 51 publications
3
40
1
8
Order By: Relevance
“…La investigación es un componente importante durante la formación del médico especialista. Su práctica permite lograr un mejor manejo clínico de los pacientes, desarrollar habilidades de apreciación crítica de artículos científi cos, fomentar el pensamiento crítico y del aprendizaje permanente, y tener una mayor satisfacción con su formación académica [1][2][3][4][5][6]. Para ello se han diseñado estrategias para impulsar la investigación durante la residencia, muchas de las cuales han tenido resultados exitosos en términos de producción científi ca y del prestigio de los programas académicos donde se han llevado a cabo [7,8].…”
Section: Introductionunclassified
“…La investigación es un componente importante durante la formación del médico especialista. Su práctica permite lograr un mejor manejo clínico de los pacientes, desarrollar habilidades de apreciación crítica de artículos científi cos, fomentar el pensamiento crítico y del aprendizaje permanente, y tener una mayor satisfacción con su formación académica [1][2][3][4][5][6]. Para ello se han diseñado estrategias para impulsar la investigación durante la residencia, muchas de las cuales han tenido resultados exitosos en términos de producción científi ca y del prestigio de los programas académicos donde se han llevado a cabo [7,8].…”
Section: Introductionunclassified
“…However, with the relatively low number of articles overall and the fact that publication number is only one measure of research experience and training during a clinical fellowship, we consider these other metrics less important in this initial exploratory analysis. Given the recent positive association found between publication track record and clinical skills assessment scores amongst residents in training, further work is needed to examine the relationship between surgical outcomes, clinical competency and research output amongst subspecialty fellows . In conclusion, we demonstrated evidence of clinical research training in our fellowship programme and recommend setting a target of one to two publications during or soon after subspecialty training for ophthalmic fellows in Australia.…”
Section: Comparison Between Wa and Rveeh Fellow Publication Outputmentioning
confidence: 62%
“…Research is an essential part of postgraduate medical training; exposure to research during residency has been shown to improve critical thinking skills, stimulate interest in academic medicine and result in better clinical performance during residency training. 12,13 By presenting their research at biomedical meetings or conferences, residents have the opportunity to critically discuss their findings, exchange research ideas and potentially establish new avenues for collaboration with established investigators. In addition, the process of converting an abstract into a full-text article and submitting it to a peer-reviewed journal offers residents practical experience in data analysis, critical appraisal and academic writing as they navigate the peer-review and publication process.…”
Section: Discussionmentioning
confidence: 99%